Microbiological Contamination of In-Store Lipstick Testers Available to the Consumer - Vassoler, Mireli; Tonial, Fabiana; Cristina Fagundes, Silvia; Alana Fagundes, Micheila; Bernarda Zortéa, Nágila; Grazziotin Rossato-Grando, Luciana; Dallazem Bertol, Charise (O Mundo da Saúde, 2020)
The microbiological contamination of pharmaceutical and cosmetic products represents a public health problem because it can cause infections. Before purchasing a particular cosmetic, many consumers test it on their own skin, increasing the susceptibility to microbiological contaminations. We hypothesize that these lipstick testers available to pharmacy consumers represent a potential source of microbiological contamination. This study analyzed the microbiological quality of 30 lipstick samples, randomly collected, from different manufacturers, available to the consumers for trials in pharmacies in southern Brazil (fifteen samples were collected in Casca, five in Ciríaco and ten in Passo Fundo). The microbiological quality of the lipsticks was evaluated by: total count of viable bacteria and mold and yeast, and presence of pathogens Staphylococcus aureus and Pseudomonas aeruginosa. It was verified that amounts ranged from 1.0 x 10¹ to 1.9 x 105 CFU/g of viable bacteria and from 1.0 x 10¹ to 7.3 x 10³ CFU/g of molds and yeasts on the lipsticks. 54.33% and 40% of the samples were disapproved by the total count of viable bacteria and molds and yeasts, respectively. S. aureus, Aspergillus sp. and Cladosporium sp. were also found. Although the waxy composition of the lipsticks hinders microbial contamination this research reveals a large number of microorganisms. Our hypothesis that the lipsticks have a high microbiological load was confirmed. Opportunistic pathogenic microorganisms can become infectious agents in patients with compromised immune systems. The use of disposable applicators is proposed as an alternative way to avoid microbiological contamination of the cosmetic products.